Integrated usage of Trichoderma harzianum and biochar to ameliorate salt stress on spinach plants. Issue 14 (6th December 2022) - Sofy, Mahmoud; Mohamed, Heba; Dawood, Mona; Abu-Elsaoud, Abdelghafar; Soliman, Mona
ABSTRACT: Salinity is among the most significant threats hindering global food security. The impact of Trichoderma, biochar, and combination on Spinach plants under salt stress conditions was investigated. Our results confirmed that salt stress (75, 150 mM) negatively affected morphological and physiological parameters of Spinach plants such as shoot (26.4%, 45.9%), and root length (16.1%, 51.2%), fresh and dry weights of root and shoot, membrane stability index (9.8%, 18.5%), relative water content(4.5%, 16.8%), chlorophyll content, mineral contents, endogenous phytohormones (auxin, gibberellins, abscisic acid, jasmonic acid, and salicylic acid) and total soluble protein content. However, electrolyte leakage, lipid peroxidation, reactive oxygen species production (such as hydrogen peroxide and hydroxyl radical), sodium, soluble sugars, proline contents, and antioxidant enzymes activities (peroxidase, catalase, and superoxide dismutase) significantly increased as a response to salt stress. The use of Trichoderma, biochar, and combination led to significant increases in all the above parameters; nevertheless, these treatments led to significant decreases in EL%, MDA, ROS, and sodium content in the stressed plants. The results proved the combination of Trichoderma and biochar is the most effective in alleviating the damaging impacts of salt on Spinach plants by increasing the up-regulation of antioxidants and decreasing membrane leakage and ROS.